Lämpötilan, valaistuksen ja kasvutiheyden vaikutus jauhosavikan (Chenopodium album L.) satoon - Erviö, Leila-Riitta (Agricultural and Food Science, 1972)
Pot experiments were carried out in phytotrons under day (20 h)—night (4 h) temperatures of 24°, 24°—14°, 12° and 12°—7° C and light intensities of 16 000 and 5 000 lux. Chenopodium album was grown in pots at densities of 50, 100, 200, 400, 800, 1 600 and 3 200 plants per m2. The plants developed faster at the high temperatures (24°, 24°—14° C) than at the low temperatures (12°, 12°—7° C). Branching was scarcer at high than at low temperatures. The leaf area index (LAI) was lowest for plants grown at 24°, slightly higher at 24°—14°, at its highest at 12°, and fell again slightly in those grown at 12°—7° C. The dry matter yield was smaller at the high than at the low temperatures. The light intensity of 16 000 lux gave rise to faster plant development and higher numbers of branches per plant than that of 5 000 lux. The low light produced leaves with a larger specific leaf area (area in relation to weight) than the leaves grown in the bright light. The total yield of plants was considerably higher but the leaves fraction proportionally smaller at 16 000 than at 5 000 lux. A steep reduction in the number of branches per plant was found when the growing density was increased from 50 to 400 plants per m2. In the same range of density the LAI increased sharply, but with more than 400 plants per m2 the increase slowed down. Temperature and light intensity had notable effects on the growth model showing the variations in yield of C. album at increasing plant densities (Figs. 3—5). Under conditions where the plants remained small the increase in yield was linear, whereas under conditions of strong vegetative growth the yield increases became smaller in dense populations due to competition between individuals.